Estimating the impact of the European wool-carder bee, Anthidium manicatum, in the northeastern United States - Graham, Kelsey. (2017)
Abstract: Invasive species can have devastating impacts on invaded communities - displacement of native species, disruption of ecosystem processes, and large economic costs. But many invasive species do not have significant impacts. It is therefore important to established direction (positive/negative) and magnitude of impact when assessing invasive species. Unfortunately, for most invasive species there are no studies on impact. This is particularly true for invasive, unmanaged bees. Therefore, this dissertation aims to fill this gap for the most widespread unmanaged bee in the world, Anthidium manicatum (the European wool-carder bee). Concerns have been raised about this bee in North America. Male A. manicatum defend flowers, and aggressive interactions can result in severe injury or death to native pollinators. Female A. manicatum are polylectic with low floral constancy, making them poor pollinators. They also remove plant trichomes for nesting material. Due to these concerns, we measured impact in five ways: (1) impact of female A. manicatum nesting behavior on the plant Stachys byzantina, (2) role of naïveté in interactions between a native pollinator, Bombus impatiens, and A. manicatum, (3) impact of A. manicatum on B. impatiens foraging behavior and fitness, (4) impact of A. manicatum on fitness of a forage crop, Vicia villosa, and (5) habitat suitability of A. manicatum. We provide evidence that female A. manicatum cause chemical changes in S. byzantina when they remove trichomes, which attracts other A. manicatum, leading to additional carding damage. We also provide evidence that A. manicatum may benefit from interspecific naïveté, and that male A. manicatum impact B. impatiens through interference competition and female A. manicatum impact B. impatiens through exploitative competition. Additionally, we provide evidence of a decrease in fitness components for Vicia villosa associated with A. manicatum. Finally, we modeled habitat suitability for A. manicatum and found an association between A. manicatum and developed habitat. Taken together, these results provide strong evidence that invasive A. manicatum are having a negative impact on the native community; however, the magnitude of impact is likely low, as we found no fitness effects in B. impatiens, and A. manicatum were rarer across invaded habitat than predicted.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Biology.; Advisor: Philip Starks.; Committee: Colin Orians, J. Michael Reed, George Ellmore, and Steven Alm.; Keyword: Ecology.